The Impact of Adjuvant Therapy on Survival and Recurrence Patterns in Women With Early-Stage Uterine Carcinosarcoma: A Multi-institutional Study. Issue 1 (January 2016) - Guttmann, David M.; Li, Hualei; Sevak, Parag; Grover, Surbhi; Jacobson, Geraldine; Feldman, Aharon; Rubin, Stephen; Chu, Christina; Bhatia, Sudershan; Elshaikh, Mohamed A.; Lin, Lilie L.
Abstract : Objective: The aim of the study was to characterize the impact of adjuvant therapy on survival in women with stage I/II uterine carcinosarcoma after primary surgery. Methods: We reviewed records of 118 consecutively treated women with 2009 International Federation of Gynecology and Obstetrics stage I/II uterine carcinosarcoma who underwent hysterectomy between 1990 and 2014 at 4 academic institutions. Patients were categorized by adjuvant treatment group into observation, chemotherapy only, radiation only, and combined chemotherapy and radiation. Survival analyses were conducted using Kaplan-Meier and Cox proportional hazards models. Results: Median follow-up was 28 months (range, 1–244 months). Lymphadenectomy was performed in 94 patients (80%). Postoperative management included observation (n = 37 [31%]), chemotherapy alone (n = 19 [16%]), radiation therapy (RT) alone (n = 24 [20%]), and combined RT and chemotherapy (n = 38 [32%]). Radiation therapy modality included vaginal brachytherapy in 22 patients, pelvic external beam RT in 21 patients, and combination in 19 patients. In 58% of women, chemotherapy consisted of carboplatin/paclitaxel. Median overall survival for all women was 97 months. On univariate analysis, adjuvant treatment group was associated with improved overall survival (hazard ratio [HR], 0.74; confidence interval [CI], 0.58–0.96; p = 0.02), freedom from vaginal recurrence (HR, 0.55; CI, 0.37–0.82]; p = 0.004), and freedom from any recurrence (HR, 0.70; CI, 0.54–0.92; p = 0.01). Pairwise comparisons demonstrated a significant benefit to chemoradiation over other adjuvant treatments. Adjuvant treatment group remained a significant covariate for all 3 end points on multivariate analysis as well. In addition, lymphadenectomy improved overall survival on multivariate analysis (HR, 0.24; CI, 0.09–0.61; p = 0.003). Of patients under observation only who had a recurrence, 8 (44%) of 18 had a recurrence in the vagina as the sole site of recurrence. By contrast, of women who received vaginal brachytherapy, significantly fewer had a recurrence in the vagina (1/42 [2.3%]; p < 0.003, log-rank test). Conclusions: In women with early-stage uterine carcinosarcoma, our data suggest superior survival end points with combined RT and chemotherapy. The frequency of vaginal recurrence suggests a role for incorporating vaginal brachytherapy in the adjuvant management of this disease.